Endurance control in 12- and 13-year-old sport walkers - Ernesto Santana García; Lázaro de la Paz Arencibia; Ana María Morales Ferrer (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
For the process of effective control of endurance in cyclical disciplines, it has been suggested to determine parameters which consider the development of this capacity according to speed. This is one of the fundamental factors that influences its manifestation and that makes the level of information about this process depend on the result of the tests used.  In addition to the particularities of these sports, the age and level of the athletes are also considered. This research is developed with the aim of proposing a specific maximum speed test for sport walking, according to the particularities of the ages between 12 and 13 years, based on the lack of references on specific speed tests for school walkers. It has an application and processing methodology for the determination of the endurance coefficient. The methods used were theoretical (analysis and synthesis, induction - deduction) and empirical (measurement, document analysis and statistical mathematics). It is started from a population made up of 8 athletes from "Ormani Arenado" Initiation Sport School (EIDE) in Pinar del Río, four of them women and 10 coaches as a source of information. As a proposal, in the 100 m sport walking test, compliance with the requirements of the competitive regulations to the correct technical execution is observed.